SURVIVAL STRATEGY FOR WOMEN WITH DISABILITIES AS HEAD OF FAMILY - juli astutik (Jurnal Perempuan dan Anak, 2019)
People with disabilities have physical limitations and mental disorders. According to Law No. 8 of 2016 concerning persons with disabilities, people with disabilities are those who experience physical, intellectual, mental and sensory limitations for a long time in interacting with the environments who may experience obstacles and difficulties in participating fully and effectively with other citizens based on equal rights. In relates to that, women with disabilities still experience some social discrimination such as social exclusion, marginalization, stereotypes and violence which may results poverty, unemployment, and life deprivation experienced by women with disabilities as heads of households. With the discrimination they experienced, women with disabilities as human beings always tries to carry out survival strategies to meet their life and family needs. Economic problems experienced by women with disabilities makes them have to carry out a survival strategy. As an analytical tool in this study, researchers used the Subsistence Ethics Theory by Scott (1989). In the Ethical Theory of Subsistence, there are three ways of survival mechanisms, among others are to tighten spending, to have a side job, and to get help from networks outside the family. Using descriptive qualitative research, data was collected through observation, interview and documentation techniques. The data was then analyzed through the process of data reduction, data presentation and verification. The data validation uses source triangulation techniques, technical triangulation and time triangulation. From the results of the study, it can be concluded that most of the research subjects used survival mechanisms by tightening expenditures in order to increase daily expenses. In addition, they have side jobs as farm laborers, odd jobs, and also tailors; as well as utilize the local government aid to meet their daily needs.